Drug prescribing in public primary care centres: Results from prescription studies 1988-1997 in the county of Halland , Sweden. - Silwer L; Johansson E; Lundborg CS (Scandinavian Journal of Primary Health Care, 2002)
Objective - To present the prescribing patterns of general practitioners (GPs) at public primary care centres (PPCCs) in Halland, a county in the south-west of Sweden. GP share of the total prescribing of different drug groups 1988-1997 is presented, as well as changes in patterns. Design - A descriptive prescription study performed 3 months each year in 10 consecutive years. Setting - Medical service and pharmacies in Halland. Subjects - Prescriptions from about 100 GPs of PPCCs and 550 physicians of various other specialties. Main outcome measures - Percentages and absolute numbers of GPs prescribing. Results - GPs prescribed 45% and 51% of the prescriptions from physicians in 1988 and 1997, respectively, while the cost shares were 40% and 42%. An increase in prescriptions was seen both in relative and in absolute numbers (from 117 414 in 3 months in 1988 to 161 012 in 1995). The increase in cost per DDD (defined daily dose) during the study period was 47% for GPs and 72% for other doctors. Conclusions - GP prescribing increased in both absolute and relative numbers, while the cost increase per DDD was moderate compared to other physicians.